Geochemical Characteristics and Quality Appraisal of Groundwater From Huatugou of the Qaidam Basin on the Tibetan Plateau - Wang, Shengbin; Xie, Zhan; Wang, Fenglin; Zhang, Yuqing; Wang, Wanping; Liu, Kui; Qi, Zexue; Zhao, Fengyun; Zhang, Guoqiang; Xiao, Yong (Frontiers in Earth Science, 2022)
Groundwater is the foremost water resource for various purposes in arid regions. The extremely arid climate makes groundwater geochemistry there evolve faster in a short distance and water supply face higher pressure of poor geochemical quality. A hyper-arid watershed on the Tibetan Plateau was investigated to get insights into the geochemical signature, formation, and quality suitability of groundwater there. A total of 13 surface water samples and 32 phreatic groundwater samples were collected for hydrogeochemical analysis. The results showed groundwater had better hydrogeochemical quality than surface water and was more favorable for human society utilization. Groundwater was dominated by relatively fresh hydrochemical facies of HCO3–Ca, mixed HCO3–Na·Ca, and mixed Cl–Mg·Ca type with more than 93% of samples having the TDS below 1,000 mg/L. Most of the groundwaters were soft fresh water (84.38%) and had excellent to good quality (93%) for domestic purposes based on entropy-weighted water quality index evaluation. Groundwater was suitable for irrigation in terms of sodium and permeability hazard, but the potential salinity hazard should be concerned. The poor geochemical quality of groundwater was ascribed to the salinity caused by strong evaporation. Natural rock–water interactions including silicate weathering, carbonate dissolution, and cation exchange were still the predominated processes governing groundwater chemical composition. The influence of human activities was very limited. Groundwater resource exploitation and management should mainly consider the salinity and strong evaporation due to shallow water depth.